MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI MEDIA AUDIO VISUAL BAGI ANAK SLOW LEARNER - Fatma Herlinda (Universitas Negeri Padang, 2014)
Abstrack: This research was conducted due to a problem indicating that a slow learner named X in class III was not able yet to read words. Therefore, the researcher tried to improve his rading ability by applying audio visual media. This was a single subject Research which applied A-B-A design. The result of the research revealed that the slow learner’s X reading improved after audio visual media applied. There were five words given to the students including table, ball, book ,pen and glass. In the baseline condition, the highest score was 20%. In the intervention condition, the highest score was 100%. In the baseline (A2) condition, the highest score was 100%. Based on these results, it was concluded that the use of audio visual media could improve the slow learner’s X reading ability in class III of SDN 07 Binuang Kampung Dalam Padang. Kata kunci: Audio Visual; Kemampuan Membaca Kata.